2015
DOI: 10.1007/s00417-015-3052-9
|View full text |Cite
|
Sign up to set email alerts
|

Birth-related retinal hemorrhages in healthy full-term newborns and their relationship to maternal, obstetric, and neonatal risk factors

Abstract: RH is common in full-term newborns. A lower prevalence of newborn RH was found in infants delivered by mothers with a history of cesarean delivery. In contrast, SVD and cephalhematoma were found to be potential risk factors for the development of newborn RH in full-term infants. Infants with these risk factors may, therefore, require greater attention in regard to RH development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 10 publications
10
27
0
Order By: Relevance
“…2, 7 The studies that have examined FH at birth report that FH are not uncommon at birth, are more frequent among infants delivered via vaginal delivery, and at times can take up to 58 days to resolve completely. 8 No study has performed universal retinal examination on a diverse group of infants such as the United States population.…”
mentioning
confidence: 99%
“…2, 7 The studies that have examined FH at birth report that FH are not uncommon at birth, are more frequent among infants delivered via vaginal delivery, and at times can take up to 58 days to resolve completely. 8 No study has performed universal retinal examination on a diverse group of infants such as the United States population.…”
mentioning
confidence: 99%
“…Retinal haemorrhages (RHs) in term newborns were discovered with a binocular indirect ophthalmoscope by Jaeger in 1861 . Later, with improvement in retinal examination techniques, RHs was found to be one of the most commonly identified eye abnormalities in term newborns . The incidence of RH varies in different reports, but is generally in the range of 2.6% to 50% .…”
Section: Introductionmentioning
confidence: 99%
“…Choi et al suggested that newborns with a history of perinatal distress were more likely to have retinal haemorrhage than healthy babies. Zhao et al found that spontaneous vaginal delivery and cephalohematoma were potential risk factors for the development of newborn RH in full‐term infants. Foetal hypoxia may cause retinal vein congestion, increased blood viscosity, leading to postnatal retinal haemorrhage…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations